2011
DOI: 10.1021/la200639b
|View full text |Cite
|
Sign up to set email alerts
|

Pulling Nanotubes from Supported Bilayers

Abstract: The force required to form a nanoscale tube from a supported lipid bilayer (SLB) by pulling was measured using an atomic force microscope (AFM). The equilibrium membrane shape during an AFM pulling experiment was calculated and used to derive a general force-distance relationship for pulling a tube from an SLB. We compare these theoretical results with our experimental data and determine the tube radius, the force required to elongate the tube, and, consequently, the surface tension. For a dioleoylphosphatidyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…AFM force spectroscopy measurements rely both on approach and retraction curves. Usually, in the case of lipid bilayers, the approach curve is used for extracting nanomechanical information but, in some cases, valuables data can also be contained in retraction curve (Dufrêne et al, 1998;Armond et al, 2011). For example, the retraction curve can provide an indication of the adhesion force between the AFM tip and the different regions of the lipid bilayer (Dufrêne et al, 1998).…”
Section: Atomic Force Spectroscopy On Supported Lipid Bilayersmentioning
confidence: 99%
“…AFM force spectroscopy measurements rely both on approach and retraction curves. Usually, in the case of lipid bilayers, the approach curve is used for extracting nanomechanical information but, in some cases, valuables data can also be contained in retraction curve (Dufrêne et al, 1998;Armond et al, 2011). For example, the retraction curve can provide an indication of the adhesion force between the AFM tip and the different regions of the lipid bilayer (Dufrêne et al, 1998).…”
Section: Atomic Force Spectroscopy On Supported Lipid Bilayersmentioning
confidence: 99%
“…This tube pulling process occurs at constant force, the tube growing force (Ftube) (Armond et al, 2011;Berta Gumí-Audenis et al, 2018;Maeda et al, 2002;Ralf P Richter & Brisson, 2003), and it is observed as a force plateau in the retract part of the force-separation curve ( Figure 5), at several tens of pN from which Ftube and the tube growing distance (d) can be recorded. Pulling lipid tubes with an AFM tip out of SLBs is a simplified but analogous situation to some biological processes involving mechanical and conformational adjustments -bending, vesiculation, tubulation-like formation of membrane tethers, endocytic vesicles, etc.…”
Section: Atomic Force Microscopy (Afm)-based Methodologymentioning
confidence: 99%
“…However, the cytoskeleton adhesion and σ are difficult terms to separate, and therefore the concept of apparent membrane tension, σapp, has been proposed to include the adhesion energy parameter γ (Sheetz, 2001), σapp= σ + γ. When the lipid tube grows under thermodynamic equilibrium, at the limit of zero velocity (static thermodynamic analysis), the following mathematical expression relates the membrane parameters mentioned above with the Ftube (Armond et al, 2011;Canham, 1970;Daillant et al, 2005;E Evans & Yeung, 1994;Berta Gumí-Audenis et al, 2018;Hochmuth et al, 1996;Marcus & Hochmuth, 2002;Roux, 2013) The plus of this approach, AFM-based pulling lipid tubes from SLBs, is that it combines the advantage of the AFM local probing with nanoscale lateral and force resolution, with the simplicity of the SLB model preparation. Besides, the local nanomechanical properties of SLBs can be explored through the combination of the tubing force spectroscopy approach and the Fb analysis exposed before, within the same experimental procedure (Berta Gumí-Audenis et al, 2018).…”
Section: Atomic Force Microscopy (Afm)-based Methodologymentioning
confidence: 99%
“…Typical marks for lipid bilayers adhering to the tip are bilayer penetration events ( Figure 3B ), a non-sharp transition when touching the surface ( Figure 3C ), or pulling of a lipid bilayer tether during retraction ( Figures 3B,C ). The latter is marked by a force plateau of 0.005–0.15 nN (Bo and Waugh, 1989 ; Armond et al, 2011 ).…”
Section: Materials and Equipmentmentioning
confidence: 99%